Validation of Phyleb-VIV Media for Training Middle School Students’ Physics Problem-Solving Skills - I Made Hermanto; Dewi Diana Paramata; Rahim Tolingguhu (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to validate Phyleb-VIV, a web-based learning medium that integrates a virtual laboratory, interactive simulations, and video-based instruction to train junior high school students’ problem-solving skills in direct-current electricity. The development research followed the ADDIE model, and this report focuses on the implementation outcomes and formative expert evaluation. Expert validation was conducted by three validators using a 1–5 Likert-type instrument across four aspects, namely Content, Appearance and Design, Language and Communication, and Interactivity and Engagement. Data were analyzed descriptively using mean Likert scores (P) and validity criteria. The results indicated that all aspects fell into the Highly Valid category, namely Content (P = 4.80), Appearance and Design (P = 5.00), Language and Communication (P = 5.00), and Interactivity and Engagement (P = 4.75). These findings confirm that Phyleb-VIV is suitable for classroom try-outs to examine its practicality and effectiveness. Recurrent qualitative feedback from validators emphasized the need for more diagnostic, topic-specific automated feedback and regular content updates to maintain relevance. In conclusion, Phyleb-VIV demonstrates excellent validity in terms of content, interface, communication, and interactivity, and is ready for further testing to evaluate its impact on improving students’ conceptual understanding and problem-solving skills in direct-current electricity.